WHEN TWO DIABETES MET: HYPERGLYCAEMIC EMERGENCY OR VASOPRESSIN DISORDER? - Kamarudin, Afifah; Ahmad, Nurul Thohirah; Oon, Jen Hoong; Karim, Nor Afidah (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Central diabetes insipidus (CDI) is caused by decreased secretion of or resistance to ADH. The clinical and laboratory findings may be similar to the hyperosmolar hyperglycaemic state (HHS). We reviewed case notes, investigation results, imaging and treatment options based on literature review. CASE A 30-year-old female with history of gestational diabetes mellitus presented with 3-day history of vomiting and fever. She also had polyuria, polydipsia and fatigue for the past 2 years. Her blood sugar level was 24.9 mmol/L, serum osmolarity was 346 mOsm/L and serum sodium was 162 mmol/L, with no acidosis or ketosis. The patient was diagnosed with HHS and received appropriate treatment. However, she continued to experience polyuria. Further investigation revealed weight gain, irregular menstrual cycles and recent absence of menstruation. Subsequent investigations revealed features of diabetes insipidus (DI) (serum sodium: 160 mmol/L, serum osmolality: 350 mOsm/kg, urine osmolality: 114 mOsm/kg). Following the administration of desmopressin, the urine osmolality increased to 505 mOsm/kg. Additional tests conducted showed normal prolactin, cortisol and thyroid function, but low IGF-1 and hypogonadotropic hypogonadism. The patient was started on regular sublingual desmopressin and her symptoms improved. She is currently awaiting an MRI of the pituitary gland. The patient's initial presentation resulted in treatment for HHS. However, subsequent investigation uncovered the presence of CDI, which has been obscured by the diabetes mellitus. In younger patients who present with CDI, hypophysitis is typically the cause, reported to occur in up to 50% of patients. \Treatment decisions should be guided by clinical evaluation and imaging, as patients with pituitary dysfunction but no mass effect and likely lymphocytic hypophysitis may be managed with medical therapy and close monitoring. CONCLUSION Clinicians should have a high index of suspicion of CDI among patients manifesting with possible HHS who do not improve despite adequate control of hyperglycemia.